Digitalizing Pesantren Economy: The Dynamics of Cashless Payment Systems and Santri Financial Behavior - Evi Sulfaningsih; Dwi Ratnasari; Muhammad Nur Najimi (LPPPM STAI Darul Hikmah Bangkalan, 2026)
The rapid development of financial technology has driven the transformation of the payment system from cash transactions to digital systems in various sectors, including Islamic educational institutions such as Pesantren. However, the implementation of a non-cash payment system in Pesantren presents unique dynamics because it involves the interaction between technological innovation, institutional governance, and Islamic economic values that are the basis of Islamic social practices. This research aims to examine the dynamics of digital financial transformation in Pesantren and synthesize the pattern of financial technology adaptation in the Pesantren economic ecosystem. This study uses a qualitative approach through the Systematic Literature Review (SLR) method, analyzing nine primary corpus articles selected through the PRISMA 2020 screening process from publications in the 2020–2025 period. The data was analyzed using thematic content analysis to identify the main patterns in the implementation of digital payment systems in Pesantren. The results of the study show three main dynamics in the digitalization of the pesantren economy, namely variations in digitalization policy typologies, gaps in infrastructure and institutional readiness, and changes in student transaction behavior influenced by the digital payment system. The cashless payment system contributes to increased transparency, financial control, and institutional accountability, but also faces challenges in the form of limited digital literacy, infrastructure gaps, and socio-cultural resistance. Theoretically, this study enriches the study of Islamic digital economy by explaining how traditional Islamic educational institutions negotiate technological modernization through the integration of fintech innovation, institutional governance, and Islamic economic values.